Traffic accidents and injury patterns in underage driving: a study from Klaten Soeradji Tirtonegoro Hospital data - Susanti, Natalia; Gizela, Beta Ahlam; Suriyanto, Rusyad Adi (Berita Kedokteran Masyarakat, 2022)
Purpose: This study aims to determine the pattern of injury, distribution of age groups, roles, gender, and the most frequent helmet use compliance among victims of child traffic accidents. Methods: The study used a descriptive method with a cross-sectional research design. The research subjects were medical records of pediatric traffic accident patients in the Emergency Room (IGD) RSUP Dr. Soeradji Tirtonegoro from January 1, 2019, to December 31, 2019. Results: From 34 cases of child motorcycle accidents in the ER Soeradji Tirtonegoro, obtained data on the distribution of children’s motorcycle accidents at RSUP Dr. Soeradji Tirtonegoro Klaten according to gender, age, the role of children, helmet use, type of injury, number of injuries, and location of the injury. Conclusion: Motorcycle traffic accidents in children are most often experienced by boys aged 16 years, the role of a driver. Most data on helmet use in children has yet to be discovered. The most common type of injury in cases of motorcycle traffic accidents in children is abrasions/vulnus excoriatum. Most cases (41%) had two injuries; the most common injury site was the lower extremity.